The Impact of E-Service Quality and Perceived Product Quality on Customer Satisfaction in Batik Keris Online Store - rizki, faizatul; wijayanti, ra afera ratna (LIAISON JOURNAL OF BEST, 2025)
The Batik Keris industry has witnessed a surge in online sales in recent years, making e-service quality and perceived product quality crucial factors influencing customer satisfaction. This study investigates the impact of e-service quality and perceived product quality on customer satisfaction in the context of Batik Keris online stores. A survey questionnaire was administered to 267 online Batik Keris customers to gather data on their perceptions of e-service quality, perceived product quality, and customer satisfaction. The findings suggest that Batik Keris online stores should prioritize e-service quality and perceived product quality to enhance customer satisfaction and foster long- term customer relationships. By providing a seamless and secure online shopping experience, offering high-quality Batik Keris products, and responding promptly to customer inquiries, businesses can effectively retain and attract customers in the competitive e-commerce landscape. E-service quality and perceived product quality have a significant impact on customer satisfaction in using Batik Keris’ online store. Based on the results, perceived product quality has more impacts on customer satisfaction as a mediating variable in e-commerce platforms. Keywords: E-Service Quality, Customer Satisfaction, Product Quality, Batik Keris, Online Store